Strabismus surgery among Medicare beneficiaries: imputed rates of reoperation in the same calendar year - Leffler, Christopher T.; Pariyadath, Allison (Digital Journal of Ophthalmology, 2016)
Purpose To compare strabismus surgery reoperation rates in a large national database of provider payments when the adjustable-suture technique was available and not available. Materials and Methods Fee-for-service payments to Medicare providers for horizontal (CPT 67311) and vertical (CPT 67314) strabismus surgery in 2012 were analyzed to identify payments for reoperations in the same calendar year. The adjustable-suture technique was considered to be available to the patient if the patient’s surgeon billed for adjustable sutures during the year. We determined the association of reoperation with the availability of the adjustable-suture technique and with surgeon volume. Results Patients having horizontal muscle surgery had a rate of reoperation in 2012 of 4.1% (15 of 364 patients) when the adjustable technique was available, compared with 7.1% (77 of 1,082 patients) when the adjustable technique was not available (P = 0.047). Patients having vertical muscle surgery had a rate of reoperation in 2012 of 4.1% (8 of 196 patients) when the adjustable technique was available, compared with 8.3% (38 of 458 patients) when the adjustable technique was not available (P = 0.07). Having surgery in a high-volume surgical practice was not reliably associated with reoperation rates. Conclusions For patients having strabismus surgery, the availability of the adjustable-suture technique was associated with a lower reoperation rate in this large national database (compared with patients for whom the adjustable technique was not available). The difference was statistically significantly different from zero for horizontal muscle surgery but not for vertical muscle surgery.